2017
DOI: 10.3390/toxins9040139
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Antimicrobial Activity and the Entomocidal Potential of Bacillus thuringiensis Isolates from Algeria

Abstract: This work represents the first initiative to analyze the distribution of B. thuringiensis in Algeria and to evaluate the biological potential of the isolates. A total of 157 isolates were recovered, with at least one isolate in 94.4% of the samples. The highest Bt index was found in samples from rhizospheric soil (0.48) and from the Mediterranean area (0.44). Most isolates showed antifungal activity (98.5%), in contrast to the few that had antibacterial activity (29.9%). A high genetic diversity was made evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 113 publications
(155 reference statements)
3
26
0
1
Order By: Relevance
“…tenebrionis DSM-2803 was shown to adversely affect the growth of Colletotrichum gloeosporioides, a potent phytopathogen that causes "anthracnose" in avocado (Persea americana), and one that is responsible for significant economic loss in México (De la Fuente-Salcido et al, 2016). Other studies have also shown the adverse effect of B. thuringiensis chitinases against F. oxysporum, the etiological agent of the fungal vascular wilt of date palm, an important traditional crop in North Africa and The Middle East (Ni et al, 2015;Djenane et al, 2017). Phytopathogenic fungi alter plant physiology and cause disease throughout development, including during seed germination.…”
Section: Application Of Chitinases To Improve the Toxic Activity Agaimentioning
confidence: 99%
“…tenebrionis DSM-2803 was shown to adversely affect the growth of Colletotrichum gloeosporioides, a potent phytopathogen that causes "anthracnose" in avocado (Persea americana), and one that is responsible for significant economic loss in México (De la Fuente-Salcido et al, 2016). Other studies have also shown the adverse effect of B. thuringiensis chitinases against F. oxysporum, the etiological agent of the fungal vascular wilt of date palm, an important traditional crop in North Africa and The Middle East (Ni et al, 2015;Djenane et al, 2017). Phytopathogenic fungi alter plant physiology and cause disease throughout development, including during seed germination.…”
Section: Application Of Chitinases To Improve the Toxic Activity Agaimentioning
confidence: 99%
“…The probiotic species of the Bacillus genus, based on full length 16S rRNA gene sequences, prevalently belong to the subsequent phylogenetic groups (clades): Bacillus subtilis group, Bacillus pumilus group and Bacillus cereus group (Table 2) (Wattiau et al, 2001;Elshaghabee et al, 2017;Lyons & Kolter, 2017). Bacillus thuringiensis, belonging to the B. cereus group (Miller et al, 2018), is in turn a biotechnological source of parasporal Cry protein (crystal), used as an agricultural biocontrol agent with insecticide activity (Ben-Dov, 2014;Djenane et al, 2017). Other strains, often found in commercial supplements of probiotic preparations for humans or for biotechnology purposes, are B. clausii or B. coagulans.…”
Section: Characteristics Of Bacillus Sp Probiotic Preparationsmentioning
confidence: 99%
“…The potential of B. thuringiensis to serve as an alternative to chemical insecticides has driven the discovery of new B. thuringiensis strains that may lead to the identification of novel protein toxins with potential use in pest management [ 1 , 6 ]. Aside from the insecticidal properties of B. thuringiensis , it has also been reported to exhibit antibacterial, antifungal, antibiofilm and emulsifying activities [ 7 , 8 ]. In general, the Bacillus species are known to be rich sources of antimicrobial compounds [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For B. thuringiensis , its antibacterial effects can be attributed to a wide range of compounds including bacteriocins and lipopeptides [ 13 ] . On the other hand, its antifungal activity has been attributed to the production of compounds such as zwittermycin, chitinase, and lipopeptides [ 7 ]. In this study, the whole genome sequence of B. thuringiensis DNG9 that was isolated from an oil-contaminated slough in Baraki-Algiers, Algeria was determined.…”
Section: Introductionmentioning
confidence: 99%